I evade taxes, and so what? : a new database and evidence from Colombia (2017)
Tax evasion lies at the core of the relationship between citizens and the state: it reflects the level of trust in the state and compliance with society's implicit 'social contract'. However, empirically analyzing it is challenging, with few direct and reliable measures. This has hampered the advancement of the theoretical and empirical literature, which is especially underdeveloped in the case of indirect tax evasion. We conduct list experiments on a large sample of households to estimate the incidence of value added tax (VAT) evasion, as well as the extent of social desirability bias in respondent answers. Around 20% of respondents engage in evasion and, surprisingly, they are not ashamed to recognize this openly. Evasion is more prevalent in places with more informality and less physical presence of the state, as well as among poorer, less educated individuals, and those who disregard the rule of law.